Educational and managerial policy making to reduce workplace violence against nurses: An action research study - Maliheh Hemati-Esmaeili; Fatemeh Heshmati-Nabavi; Zohre Pouresmail; SeyedReza Mazlom; Hamidreza Reihani (Wolters Kluwer Medknow Publications, 2018)
Background: The level of occupational violence against nurses increases from 68.8 to 98.6 percent, which is a considerable rate among healthcare settings. To create a safe environment for patient care in the emergency department (ED), a comprehensive program for the prevention of violence is necessary. The aim of this study was to plan a workplace violence prevention program (WVPP) to reduce the level of patients' and their families' violence against nurses. Materials and Methods: The present study is a quantitative part of a participatory action research project conducted in an 18-month period from October 2012 to May 2014 in an ED of Iran. In the diagnosing phase, we used quantitative and qualitative approaches. The second and third phases were assigned to design and implementation of WVPP involving a combination of educational and managerial interventions. In the evaluation phase, frequencies of patients' and their families' violence against nurses and nurses' fear of violence were measured. Results: Mc-Nemar test showed that 85.70% (n = 42) frequencies of verbal violence before implementing WVPP significantly decreased to 57.10% (n = 28) after implementing WVPP (p = 0.007). Statistical-dependent t-test (p < 0.001) indicated a significant difference in the mean (SD) scores of nurses' fear of violence before 46.10 (8.3) and after intervention 34.30 (4.6). Conclusions: Applying educational and managerial interventions was effective in reduction of workplace violence. Thus, it is recommended to include a combined approach in designing WVPP in cultures similar to Iran and pay attention to effective interactions with patients' family.